Syphilis hospital morbimortality in Brazil from 2012 to 2021 (Research, Society and Development, 2023)
Syphilis is a Sexually Transmitted Infection (STI) that represents an important public health problem. This pathology can affect all age groups and is present in all countries, regardless of their economic and social development. Despite this, most syphilis-related cases occur in low- and middle-income countries, with variations in prevalence and incidence within each country. In Brazil, studies on in-hospital morbidity and mortality from syphilis are scarce, of a local scope or restricted to a short period of analysis. This study aimed to trace the profile of hospital morbidity and mortality of syphilis in the country. This is an ecological study with data on syphilis between the years 2012 and 2021. Data were collected in the SUS information system - TABNET DATASUS according to sociodemographic variables. In addition, the present work aims to analyze socioeconomic inequalities and the access and use of health services and their relationship with inequalities in the risk of death between regions, FU and gender and age groups in the country, since knowing this profile, it allows for a better management of the disease, through the epidemiological basis that allows improvement in the implementation and development of public health policies aimed at the prevention, diagnosis and treatment of syphilis.